Organic Greenhouse Container Herb Production in South Florida: Fertilizer and Potting Media - Kati W. Migliaccio; Teresa Olczyk; Yun Qian; Yuncong Li; George J. Hochmuth; Robert C. Hochmuth; Danielle D. Treadwell; Eric H. Simonne; Lance S. Osborne; Richard K. Sprenkel (EDIS)
ABE-373, a 6-page report by K. W. Migliaccio, T. Olczyk, Y. Qian, Y. Li, G. J. Hochmuth, R. C. Hochmuth, D. D. Treadwell, E. H. Simonne, L. S. Osborne, and R. K. Sprenkel, presents the results of trials conducted in 2005 and 2006 to compare organic fertilizers and potting media for greenhouse production of container herbs. Includes references. Published by the UF Department of Agricultural and Biological Engineering, May 2007.